2020
DOI: 10.3390/healthcare8040458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Handgrip Strength on 10-Year Cardiovascular Risk among the Korean Middle-Aged Population: The Korea National Health and Nutrition Examination Survey 2014

Abstract: Handgrip strength is a simple, inexpensive health status indicator and can be used to assess mortality rate and cardiovascular disease (CVD) risk. This study used data from the Sixth Korea National Health and Nutrition Examination Survey (2014) to determine the effective use of handgrip strength to predict CVD risk. We analyzed data from 2427 adults aged from 40 to 64 years without CVD at baseline. Relative handgrip strength was calculated as the sum of the maximal absolute handgrip strength of both hands divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…A study using the Framingham Risk Score to determine the 10-year risk of CVD among middle-aged women found that increasing relative grip strength was associated with a decreased 10year risk of cardiovascular events. 59 Menopause is an important life stage for women characterized by hormonal changes and changes in cardiovascular risk factors. Additionally, monitoring relative grip strength could be a simple and cost-effective way to identify individuals at higher risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study using the Framingham Risk Score to determine the 10-year risk of CVD among middle-aged women found that increasing relative grip strength was associated with a decreased 10year risk of cardiovascular events. 59 Menopause is an important life stage for women characterized by hormonal changes and changes in cardiovascular risk factors. Additionally, monitoring relative grip strength could be a simple and cost-effective way to identify individuals at higher risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…A study using the Framingham Risk Score to determine the 10-year risk of CVD among middle-aged women found that increasing relative grip strength was associated with a decreased 10-year risk of cardiovascular events. 59 …”
Section: Discussionmentioning
confidence: 99%
“…In a study of Korean subjects, Kim et al [24] demonstrated that low grip strength in postmenopausal women is associated with low bone density and increased risk of future fragility fractures. Shim & Yoo [25] reported that for each 1 kg increase in grip strength, the 10-year cardiovascular disease risk decreases. However, Lee et al [26] pointed out that grip strength increase is associated with a decreased cardiovascular disease risk in young and middle-aged individuals, but not in the elderly; there- Alternatively, there was no significant difference in the mortality rate according to the grip strength of the dominant hand.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ED was indicated by IIEF-5 scores that were equal or less than 21. The severity of ED was further categorised based on the IIEF-5 scores: severe (5-7), moderate (8-11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21), and no ED (22)(23)(24)(25).…”
Section: Study Instrumentsmentioning
confidence: 99%
“…The majority of evidences suggested that aerobic exercises has bene cial effects on CVD risks and continue to be the most common exercise prescription (11). On the other hand, resistance training exercises have different physiologic effects, that it improves muscle strength and appears to have positive effects on chronic heart failure (14), frailty (15), osteoporosis (16), and CVD risks (17).…”
Section: Introductionmentioning
confidence: 99%